2013
DOI: 10.1111/vru.12072
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Closure Times for Cranial Base Synchondroses in Mesaticephalic, Brachycephalic, and Cavalier King Charles Spaniel Dogs

Abstract: Premature closure of cranial base synchondroses has been proposed as the mechanism for brachycephaly in dogs and caudal occipital malformation syndrome (COMS) in Cavalier King Charles Spaniels. The purpose of this retrospective study was to compare times of closure for cranial base synchondroses in mesaticephalic, brachycephalic, and Cavalier King Charles Spaniel dogs. Cranial magnetic resonance imaging studies were retrieved for client-owned dogs less than 18 months of age. Breed, age, skull conformation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…The great amount of closing and closed basispheno‐presphenoid synchondroses in airorhynch breeds complements the findings of a study on closure times of cranial base synchondroses in different domestic dog breeds up to 18 months. Schmidt et al () found that the probability of finding a closed spheno‐occipital synchondrosis at a given age was significantly higher in the brachycephalic breeds when compared with the mesocephalic ones. Facial hypoplasia in combination with prematurely fused cranial base synchondroses has also been reported for other species, for example, cattle (Julian et al, ), mice (Chen et al, ), and humans (Cohen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The great amount of closing and closed basispheno‐presphenoid synchondroses in airorhynch breeds complements the findings of a study on closure times of cranial base synchondroses in different domestic dog breeds up to 18 months. Schmidt et al () found that the probability of finding a closed spheno‐occipital synchondrosis at a given age was significantly higher in the brachycephalic breeds when compared with the mesocephalic ones. Facial hypoplasia in combination with prematurely fused cranial base synchondroses has also been reported for other species, for example, cattle (Julian et al, ), mice (Chen et al, ), and humans (Cohen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, magnetic resonance imaging and computed tomography scans were used to monitor the ossification of cranial base synchondroses. Although the scope of their study was limited, the authors reported that the sphenooccipital synchondrosis closes significantly earlier among CBa breed dogs (Figures 4 and 5) (Schmidt et al 2013). The CBa findings are interesting in the context of human pathology: For unclear reasons, craniosynostosis is often correlated with precocious closure of cranial base synchodroses (Tannenbaum et al 1983).…”
Section: Skull and Axial Skeletonmentioning
confidence: 98%
“…The spheno-occipital synchondrosis makes a significant contribution to growth post-natally [12]. A recent study found that the spheno-occipital synchondrosis was closed in 80% of dogs at 4 months old and that this suture seemed to ossify earlier in Cavalier King Charles spaniels compared to other brachycephalic dogs, which in turn ossified earlier than mesaticephalic dogs [15]. The cranial base is angled at the level of the hypophyseal fossa where the rostral prechordal and caudal chordal parts meet.…”
Section: Introductionmentioning
confidence: 99%